Prototype of enterprise network infrastructure: scalability and operational continuity - López , Sergio (2025)
The document presents a project carried out at the Universidad Técnica Nacional (UTN) in Costa Rica, where a prototype design for technological infrastructure was developed to enhance business operability, security, and continuity of operations while being robust and scalable. A qualitative methodology, which is multimethod, was used. This included the documentary analysis of information from various network infrastructures and expert judgment through feedback. These inputs were used to develop the prototype in two phases: planning and validation, followed by implementation. Key services such as DHCP, Active Directory, and backup servers were implemented, along with security measures such as physical firewalls and wireless backup servers. Collaboration with experts and periodic validation were essential to ensure the effectiveness of the design, which promises to be replicable in other medium and large-sized companies, transforming their technological infrastructure with advanced technologies and cutting-edge security measures.